Genome Skimming Contributes to Clarifying Species Limits in Paris Section Axiparis (Melanthiaceae) - Ji, Yunheng; Yang, Jin; Landis, Jacob B.; Wang, Shuying; Jin, Lei; Xie, Pingxuan; Liu, Haiyang; Yang, Jun-Bo; Yi, Ting-Shuang (Frontiers in Plant Science, 2022)
Paris L. section Axiparis H. Li (Melanthiaceae) is a taxonomically perplexing taxon with considerable confusion regarding species delimitation. Based on the analyses of morphology and geographic distribution of each species currently recognized in the taxon, we propose a revision scheme that reduces the number of species in P. sect. Axiparis from nine to two. To verify this taxonomic proposal, we employed a genome skimming approach to recover the plastid genomes (plastomes) and nuclear ribosomal DNA (nrDNA) regions of 51 individual plants across the nine described species of P. sect. Axiparis by sampling multiple accessions per species. The species boundaries within P. sect. Axiparis were explored using phylogenetic inference and three different sequence-based species delimitation methods (ABGD, mPTP, and SDP). The mutually reinforcing results indicate that there are two species-level taxonomic units in P. sect. Axiparis (Paris forrestii s.l. and P. vaniotii s.l.) that exhibit morphological uniqueness, non-overlapping distribution, genetic distinctiveness, and potential reproductive isolation, providing strong support to the proposed species delimitation scheme. This study confirms that previous morphology-based taxonomy overemphasized intraspecific and minor morphological differences to delineate species boundaries, therefore resulting in an overestimation of the true species diversity of P. sect. Axiparis. The findings clarify species limits and will facilitate robust taxonomic revision in P. sect. Axiparis.